Analysis of the effect of radio frequency interference on the DC performance of CMOS operational amplifiers - Abuelma’atti, M.T. (2003)
Fourier-series approximations are obtained for the input-output characteristic of the CMOS asymmetrical differential amplifier. Using these approximations, the DC voltage offset of a CMOS differential amplifier subjected to RF interference can be studied and analytical expressions are obtained. These expressions can help in optimizing the parameters of the CMOS differential amplifier to minimize the offset voltage resulting from the RF interference.